Proposal for fiber-optic data acquisition system for Baikal-GVD. (19th November 2021) - Allakhverdyan, V.A.; Avrorin, A.D.; Avrorin, A.V.; Aynutdinov, V.M.; Bannasch, R.; Bardаčová, Z.; Belolaptikov, I.A.; Borina, I.V.; Brudanin, V.B.; Budnev, N.M.; Dik, V.Y.; Domogatsky, G.V.; et al.
Abstract: The first stage of the construction of the Baikal-GVD deep underwater neutrino telescope is planned to be completed in 2024. For the second stage of the detector deployment, a data acquisition system based on fiber-optic technologies has been proposed, which will allow for increased data throughput and more flexible trigger conditions. A dedicated test facility has been built and deployed at the Baikal-GVD site to test the new technological solutions. We present the principles of operation and results of tests of the new data acquisition system.